Hubungan Teknik Meneran Yang Benar Dengan Kelancaran Persalinan Kala II Pada Ibu Primigravida - Bahar, Nuraisyah (Jurnal Asuhan Ibu dan Anak, 2024)
Childbirth is the removal of the results of conception (fetus and placenta) that have been full term or can live outside the womb through the birth canal or other means, with assistance or without assistance (own strength). This process begins with the presence of true labor contractions, which are characterized by progressive changes in the cervix and end with the birth of the placenta. The success of the delivery process is influenced by several factors, namely power, passage, passenger, psychology, the location of the placenta, labor helpers, and the correct way to deliver. Stretching is the stage when the opening or dilation of the cervix reaches its peak, which is 10 cm. At that time the concentration feels stronger and the mother will instinctively feel a strong urge to strain to push the baby out, with the correct pressing technique the baby can be pushed out without the need to drain energy. The purpose of this study was to determine the relationship between correct straining techniques and smooth delivery of kala II in primigravida mothers. The research method used was cross sectional, with the subject of research 30 primigravida mothers who were in labor at II, in the implementation of the study using checklist sheets as an observation tool. The data analysis used is the chi-square test. Based on the results of data analysis, it was obtained that 25 mothers (83.3%) of the 25 mothers whose labor went smoothly as much as 24 (80%) and those who did not smoothly as much as 1 (3.3%), than mothers with the wrong pressing technique as many as 5 (16.7%) all experienced labor unsmoothness. Based on the results of the study, it was concluded that there was a relation with proper smoothness labor stage ii women primigravida with the results of the chi-square p test < ?. Keywords: Smoothness Labor, Techniques Straining